2019
DOI: 10.1097/olq.0000000000000940
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Macrolide Resistance, and Fluoroquinolone Resistance in Mycoplasma genitalium in Men Who Have Sex With Men Attending an Sexually Transmitted Disease Clinic in Dublin, Ireland in 2017–2018

Abstract: This is the first prevalence study of Mycoplasma genitalium and antimicrobial resistance study in Ireland. In urine samples from men who have sex with men (n = 400) attending a sexually transmitted disease clinic in Dublin, the prevalence of M. genitalium was 3% (12 of 400 specimens; 95% confidence interval, 1.3–4.7%), and the prevalences of macrolide resistance (75%), fluoroquinolone resistance (33.3%), and multidrug resistance (33.3%) were very high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…Furthermore, most of the patients belong to the group of MSM and/or HIV-positives considered as risk populations for infections with this pathogen. In recent studies, the prevalence of M. genitalium in both groups ranged between 3% and 17% [3,[12][13][14][15]. To our knowledge, this is the first study determining mgpB types among patients strongly predominated by MSM.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, most of the patients belong to the group of MSM and/or HIV-positives considered as risk populations for infections with this pathogen. In recent studies, the prevalence of M. genitalium in both groups ranged between 3% and 17% [3,[12][13][14][15]. To our knowledge, this is the first study determining mgpB types among patients strongly predominated by MSM.…”
Section: Discussionmentioning
confidence: 74%
“…Treatment of M. genitalium with azithromycin as first-line agent is still recommended in most guidelines, 8,9 even though macrolide resistance-associated mutations have been reported to be as high as 80% in certain regions and populations. 3,10,11 Resistance levels against macrolides are higher in MSM than among women and heterosexual men, possibly caused by the frequent exposure to azithromycin for the treatment of other STIs including Chlamydia trachomatis. 12 Recent guidelines from the United Kingdom and Australia advise to treat patients with a symptomatic uncomplicated M. genitalium infection with doxycycline followed by a course of azithromycin.…”
Section: Introductionmentioning
confidence: 99%
“…Results of recent studies from England, France, Russia/Estonia, Scandinavian countries and Spain demonstrated rates of quinolone resistance of 5%, 6%, 6%, 7%, and 8%, respectively [32][33][34][35][36]. Among MSM in Ireland, 33% of M. genitalium strains are quinolone-resistant [37] and in the above-mentioned German investigation, a rate of 13% was calculated [22]. Further studies have to clear, whether the different amino acid changes described in the QRDR of ParC influence the susceptibility of M. genitalium strains to quinolones.…”
Section: Discussionmentioning
confidence: 99%